Evaluation of the addition of turmeric Curcuma longa Linn. extract in diet for biochemical blood and growth performance of giant gourami Osphronemus goramy Lacepede, 1801 - Putri Pratamaningrum Arifin; Mia Setiawati; Nur Bambang Priyo Utomo (Masyarakat Iktiologi Indonesia (Indonesian Ichthyological Society), 2016)
Giant gourami (Osphronemus goramy) has a relatively slow growth. One way to increase the growth of giant gourami is to provide additional materials (feed additives). The active substance curcumin in turmeric can stimulates the gall bladder wall to secrete bile and essential oils to prevent excessive stomach acid secretion. This study aimed to evaluate the different dose of turmeric extract in the feed that can affect digestive enzymes and growth performance of giant gourami. The turmeric extract mixed into the diet with 4 doses i.e.: 0 (control); 0.05; 0.10; and 0.15%. Fishes (4.20±0.08 g) were reared in 12 aquariums (50 x 40 x 35 cm3) with density of 10 fishes in 40 L for 60 days. Fishes were reared with recirculating system using top filter and fed at satiation two times daily at 08.00 and 16.00. Some parameters were measured including blood biochemistry (cholesterol, triglycerides, HDL, LDL and glucose), feeding consumption, specific growth rate, feed efficiency, survival rate, protein retention, lipid retention, hepatosomatic index (HSI), lipid content of liver, and glycogen content of liver. Experimental design was set according to completely randomized design with 4 treatments and 3 replications. Data growth performance and liver parameters were statistically analysed by ANOVA (one-way analysis of variance) using SPSS 17.0. The significant parameters (p<0.05) then analysed by Tukey’s test. The blood biochemical parameters (cholesterol, triglycerides, HDL, LDL and glucose) were descriptively analysed. The result showed that turmeric extract 0.15% in the feed could affect the blood biochemistry but not the growth performance of giant gourami. Abstrak Ikan gurame (Osphronemus goramy) memiliki pertumbuhan yang relatif lambat. Salah satu cara untuk meningkatkan pertumbuhan ikan gurame dengan memberikan bahan tambahan. Kunyit memiliki zat aktif kurkumin yang merangsang dinding kantung empedu untuk mengeluarkan cairan empedu dan minyak atsiri mencegah keluarnya asam lambung yang berlebihan. Penelitian ini bertujuan untuk mengevaluasi pemberian ekstrak kunyit dengan dosis yang berbeda pada pakan yang dapat memengaruhi biokimia darah dan kinerja pertumbuhan ikan gurame. Ekstrak kunyit dicampurkan ke dalam pakan dengan 4 dosis yaitu: 0; 0,05; 0,1; dan 0,15%. Ikan gurame (4,20±0,08 g) dipelihara dalam 12 akuarium (50 x 40 x 35 cm3) dengan kepadatan 10 ekor dalam 40 L selama 60 hari. Ikan dipelihara menggunakan sistem resirkulasi top filter dan diberi pakan secara at satiation sebanyak dua kali sehari pada pukul 08.00 dan 16.00. Parameter uji yang diamati yaitu biokimia darah (kolesterol, trigliserida, HDL, LDL, dan glukosa), jumlah konsumsi pakan, laju pertumbuhan harian, efisiensi pakan, kelangsungan hidup, retensi protein, retensi lemak, indeks hepato-somatik, kadar lemak hati, dan kadar glikogen hati. Rancangan yang digunakan dalam penelitian ini adalah rancangan acak lengkap dengan empat perlakuan dan tiga ulangan. Data kinerja pertumbuhan dan parameter hati dianalisis secara statistik dengan ANOVA menggunakan program SPSS 17.0. Parameter yang berbeda nyata (p<0,05) dilakukan uji lanjut menggunakan analisis Tukey. Parameter biokimia darah dianalisis secara deskriptif. Hasil penelitian menunjukkan bahwa pemberian ekstrak kunyit 0,15% pada pakan dapat memengaruhi biokimia darah tetapi tidak memengaruhi kinerja pertumbuhan ikan gurame.